Android-based learning media development with iSpring Suite application in pastry course - Febri Ananda; Elida Elida; Kasmita Kasmita; Dedy Irfan (Jurnal Pendidikan Vokasi, 2023)
The utilization of Information and Communication Technology (ICT) is one of the things needed in the education era for effective learning. This study aims to produce Android application-based media using iSpring Suite in feasible pastry courses based on the values and tests of validity, practicality, and effectiveness. The development research used the 4D model (Define, Design, Develop, and Disseminate). The limited trial of Android application media was conducted on 30 Department of Family Welfare Science, Concentration of Catering students at Universitas Negeri Padang who were taking pastry courses. Data collection instruments used validation sheets, evaluation questions, and student response questionnaires. The data obtained were analyzed descriptively and quantitatively. The results showed that the validation value of the material expert was 0.758 with the valid category, and the validation of the media expert was 0.833 with the valid category. The practicality value gets a score of 3.06 with a practical category. The effectiveness value is obtained from the evaluation results of the control class and the experimental class. Hypothesis testing was carried out using the t-test with the Independent Samples Test method. The t-test results show the t-count value (12.0228) > t-table (2.0167), so Ho is accepted. This means there is a difference in the value of the control and experimental classes. The effect size calculation obtained a value of 3.13, so based on the applicable criteria, this effect size value is included in the very high category. Based on these results, the application-based learning media using iSpring Suite is declared feasible based on validity, practicality, and effectiveness as a learning media.